PROSPECTS OF USING A COMBINATION OF LOCALLY INJECTED NON-STEROIDAL ANTI-INFLAMMATORY DRUGS AND OPIOIDS IN PERIPHERAL PAIN MANAGEMENT - YU. А. KOLESNIKOV (Вестник анестезиологии и реаниматологии)
The article reviews scientific literature on serious side effects of non-steroidal anti-inflammatory drugs (NSAIDs) and opioid analgesics widely used to treat acute and chronic pain. In order to reduce the incidence of side effects in clinical practice, oral combinations of NSAIDs and opioids are used. Unfortunately, the efficacy and safety of these combinations also do not meet contemporary requirements for analgesics. Local use of NSAIDs and opioids is one of the alternatives, which will reduce the dose of systemically administered drugs. Peripheral mechanisms play a key role in systemic mu-opioid analgesia. The use of these mechanisms when developing medication for pain relief offers promising prospects in the treatment of acute and chronic pain.